2023
DOI: 10.3390/s23073372
|View full text |Cite
|
Sign up to set email alerts
|

Design of Meat Product Safety Information Chain Traceability System Based on UHF RFID

Abstract: As a result of the current imperfection of the meat traceability system, there have been numerous food safety events with serious consequences. In this paper, a meat product information traceability system is designed to efficiently prevent such problems. This system develops an identification tag information reader based on ultra-high frequency (UHF) Radio Frequency Identification (RFID). It is compatible with LoRa wireless, USB serial port, RS485, and RJ45 Ethernet connection. Among them, the efficiency anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…This feature allows the ongoing monitoring and tracking of objects following their identification. An essential advantage of RFID technology is its ability to read tags in challenging conditions, such as snowy, foggy, or harsh environments, with rapid recognition speed [44]. RFID chips can be directly applied to animals after slaughter and before they enter the washing area.…”
Section: ) Proposed Improvements For Meeting Pilgrims' Demandsmentioning
confidence: 99%
“…This feature allows the ongoing monitoring and tracking of objects following their identification. An essential advantage of RFID technology is its ability to read tags in challenging conditions, such as snowy, foggy, or harsh environments, with rapid recognition speed [44]. RFID chips can be directly applied to animals after slaughter and before they enter the washing area.…”
Section: ) Proposed Improvements For Meeting Pilgrims' Demandsmentioning
confidence: 99%
“…Studies have shown that the use of UHF RFID tags does not affect the preservation quality of red blood cells, platelets or frozen plasma [7][8][9]. To this end, we followed the ISO18000-6C and ISBT128 standards and used a UHF RFID blood bag tag [2,10,11].…”
Section: Use Of Ultra-high Frequency Rfid Tagsmentioning
confidence: 99%
“…Each stage presents the recorded contents, such as the production, delivery, and other incidental records at the production stage; the stock, manufacturing and processing, and delivery records (containing the signature of the manufacturing responsible person, expiration date, and production line number) at the processing stage; the product stock records, production and processing schedules, delivery, and other records at the distribution stage; and finally the product stock and sales records at the retail stage 4 . By regulating the recorded contents, the information and data of production, handling, processing, distribution, and sales can be reserved and traceable for the entire process to further guarantee food safety from a farm to a dining table 5 7 .…”
Section: Introductionmentioning
confidence: 99%